Moderasi Relasi Lintas Agama Tau Samawa (Orang Sumbawa) Berbasis Keseharian di Tana Sumbawa - Yaspis Edgar Funay (Jurnal Sosiologi Agama, 2020)
This paper will analyze the interfaith relations based on people’s daily life patterns in Tana Sumbawa. Deeper, the author tries to see how a cultural-based lifestyle in society can also be one of the strengths and the closest way out to maintain community relations when they want to conflict or create post-conflict reconciliation. This paper draws a tentative conclusion that the original culture of the Sumbawa people can be a reconciliation of ideological conflicts and strengthen collective awareness because they have ethical values, morals, and good behavior as local products. Using a sociological perspective this paper examines the extent to which cultural values play a role in interfaith relations in Sumbawa. In the final part, this paper will explore the concept of Sumbawa culture as outlined in local philosophy as a concept of tolerance between religious communities in order to maintain the existence of the local cultural heritage.